Design and Research of Air-core Reactor for Middle-low-speed Maglev Train - WU Fu-Lian; LU Li; XIANG Kun; CHEN Li; SHEN Chen-Bing (机车电传动)
Development of air-core reactor for middle-low-speed maglev train was introduced. Key technology of air-core reactor was described, inductance calculation, structure design, temperature-rising and shielding-plate calculation of which were analyzed in emphasis. Simulation analysis on electromagnetic field with ANSOFT finite element software and three-dimensional modeling was carried out for reaching the national standard of non-ionizing radiation.